Efektivitas Lembaga Penyelenggara Pemilihan Umum Serentak 2019: Evaluasi Menyongsong Pemilu Serentak 2024 - Wahdini, Muhammad (Jurnal Bina Praja, 2022)
The Presidential, Vice Presidential, and Legislative General Elections were held simultaneously for the first time in 2019 as a constitutional implication of the Constitutional Court Decision Number 14/PUU-XI/2013 and the enactment of Law Number 7 of 2017 concerning General Sorting. This study aims to identify the extent of the effectiveness of The General Election Supervisory Agency in the first simultaneous implementation as an effort to face the simultaneous general election in 2024 so that it can run optimally and minimize the occurrence of errors in the general election organizing sector. The method used in this study focuses on collecting data so that this research design is descriptive qualitative. In practice, there are still many problems that occur in the organizers of the General Election. Election organizers established by law are the General Election Commissions, The General Election Supervisory Agency and the Election Organizer Ethics Council In the context of the effectiveness of the General Election Supervisory Agency. In general, the General Election Supervisory Agency has carried out its duties to the fullest, still leaving a record that it is not yet effective. The General Election Commissions as technical organizers in the General Election noted very crucial problems such as human resources that were not directly proportional to the workload carried out, causing many to get sick and even die, besides that the Permanent Voters List is still a crucial problem in the 2019 simultaneous general election, asynchronous Permanent Voters List so that millions of people cannot cast their ballots. Various administrative sectors that also experienced many problems are still being evaluated. The General Election Supervisory Agency is experiencing problems with violations and crimes that occur in the implementation of general elections are also not maximized. The Election Organizer Ethics Council which is authorized to follow up on ethical code issues tends to be considered successful, although it still leaves a record for improvement. Facing the simultaneous general election in 2024, then a comprehensive evaluation of these problems will be treated.